The impact of cash and food transfers: Evidence from a randomized intervention in Niger - Hoddinott, John F.; Sandström, Susanna; Upton, Joanna (International Food Policy Research Institute, 2014)
There is little rigorous evidence on the comparative impacts of cash and food transfers on food security and food-related outcomes. We assess the relative impacts of receiving cash versus food transfers using a randomized design. Drawing on data collected in eastern Niger, we find that households randomized to receive a food basket experienced larger, positive impacts on measures of food consumption and diet quality than those receiving the cash transfer.